Development of Precision Feed Technology Model for Ruminant Livestock Based on Nutritional Sensors - Hajar Hajar; Inal Inal; Awal Maulid Sari; La Oge (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2026)
Feeding is a key factor in ruminant livestock production systems, often ignoring the variations in individual nutritional needs of livestock, reducing efficiency and increasing feed waste. Therefore, this study aims to examine and develop a precision feeding technology model concept for ruminant livestock based on nutritional sensors through a descriptive-interpretive approach based on the latest scientific literature. The results show that the use of nutritional sensors, rumen sensors, feed consumption sensors, and feeding behavior sensors allows for real-time monitoring of livestock physiological conditions and nutritional status. Integration of sensor data into an adaptive nutrition model has been shown to improve the accuracy of estimating individual nutritional requirements, reduce the risk of overfeeding and underfeeding, and increase feed efficiency. Further discussion shows that although precision feeding technology has developed rapidly, its application is still dominated by intensive livestock systems in developed countries.